Sosialisasi Gerakan Seni Tunggal Pencak Silat Pada Siswa SMA Insan Cendekia - Muslim Bin Ilyas; Imam Suyudi; Wahyudin; Muhammad Qasash Hasyim; Andi Sahrul Jahrir (LITERA ABDI: Jurnal Pengabdian Masyarakat, 2026)
The socialization activity of the single artistic movement of pencak silat for students of SMA Insan Cendekia aimed to improve students’ knowledge, understanding, and interest in pencak silat as an Indonesian cultural heritage as well as a medium for character building among students. This activity involved 50 students and was conducted through lecture methods, demonstrations, direct practice, discussions, and question-and-answer sessions. The materials presented included an introduction to pencak silat, character values contained in pencak silat, and practice of the basic movements of single artistic pencak silat. The results of the activity showed that the students demonstrated high enthusiasm during the socialization program. Before the activity was conducted, most participants had limited understanding of the single artistic form of pencak silat. After participating in the program, students began to understand that pencak silat is not only a martial art sport but also contains elements of art, culture, discipline, sportsmanship, and self-control. In addition, students were able to practice the basic movements of single artistic pencak silat quite well under the guidance of the instructors. This socialization activity also had a positive impact on increasing students’ self-confidence, cooperation, and awareness in preserving local culture. Through this activity, students gained new experiences that could support the development of positive character while fostering a sense of love for Indonesian cultural heritage. Therefore, the socialization of single artistic pencak silat movements can serve as an alternative educational activity in schools to support cultural preservation and character development among students